PENERAPAN MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR PASSING PERMAINAN SEPAK BOLA - Galih Pratama; Fitriana Puspa Hidasari; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe formulation of the problem in this study was whether there is an increase in student learning outcomes towards the passing of football games in Class VII of SMP Negeri 7 Sungai Raya using the Cooperative Learning Model Type Student Teams Achievement Division? The purpose of this study was to describe an increase in student learning outcomes in physical education learning. The research used in the research was Class Action Research with action methods and experimental PTK types, Subjects were 26 students consisting of 14 women and 12 men and conducted at SMP 7 Sungai Raya, Kuburaya Regency. Based on the analysis of the data and the results of the study there is an increase in the passing learning outcomes of football games the data obtained were pre-cycle with an average value of 72.30, cycle 1 with an average value of 74.61, and cycle 2 with an average value of 85.12.Keywords: Football Passing, Learning Outcomes, Student Teams Achievement Division